The Application of an Implicit Enumeration Algorithm to the School Desegregation Problem - Liggett, Robin Segerblom (Management science, 1973)
This paper presents an implicit enumeration algorithm for redrawing school attendance boundaries in order to meet integration requirements. The basis of the approach is the division of the city into smaller areas or zones corresponding to neighborhoods. These zones are assigned to schools with the objective of minimizing the required bussing while meeting the school capacity and racial mix constraints. An entire zone is assigned to one school, thus preserving the neighborhood school concept. Viewing the possible zone-school assignments as a combinatorial problem, a general enumerative procedure is combined with probability theory to form the implicit enumeration algorithm. An explanation of the algorithm along with computational results of an application of the method to an existing school system is presented.